Mental health resources for NCAA student-athletes - Everritt, Megan; Rundio, Amy (London : Human Kinetics, Inc., 2023)
Alyssa Williams, the Student-Athlete Advisory Committee (SAAC) president at Oak Grove University (OGU), wants to meet with the assistant athletic director after conversing with the Student-Athlete Advisory Committee group dedicated to student-athlete well-being. Alyssa meets with Dr. Nora Coleman to discuss how student-athletes want more resources to support mental health conditions at Oak Grove University. Dr. Coleman agrees and asks Alyssa to readdress the Student-Athlete Advisory Committee group so they can identify the mental factors affecting them and to compare and contrast using internal and external resources. After ﬁnding this information, Alyssa will have a follow-up meeting with Dr. Coleman to make a proposal and address the university’s athletic board. Keywords: college athletics, mental well-being, mental health services.
Description based on XML content.
Keywords: elektronické knihy; electronic books; College athletes -- Mental health services -- Case studies